Study of Effect of Weight Ratio on Copolymerization of Chitosan and Acrylamide - Eliza Eliza; Ady Mara; Fahma Riyanti; Desnelli Desnelli (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
The use of chitosan as adsorbent in wastewater treatment has received a lot of attention. This is because the price of chitosan is cheap and easy to obtain. The application of chitosan as an adsorbent has the disadvantage of being soluble in acidic medium (pH <6.5), insoluble in water and organic solvents. Other disadvantages of chitosan are low adsorption capacity, and lack of selectivity. In this research, chitosan copolymer synthesis with acrylamide has been carried out by varying chitosan and acrylamide, namely 1:1, 2: 3 and 3: 2 using a microwave oven. The copolymers were characterized using FTIR, XRD, SEM and TGA/DTA. The results of the synthesis of chitosan copolymer with acrylamide were obtained the largest percentage of grafting at a ratio of 2: 3. From the results of FTIR analysis showed that the copolymer had been successfully synthesized. XRD analysis showed that the copolymers synthesized have amorphous properties compared to chitosan. The results of SEM analysis, the copolymers had a porous structure. Thermal analysis showed that the copolymers have better thermal stability than chitosan. The chitosan-acrylamide copolymer which was synthesized in a ratio of 2: 3 has better properties.